Scale-Up of the Manufacturing Process To Produce Docetaxel-Loaded mPEG-b-p(HPMA-Bz) Block Copolymer Micelles for Pharmaceutical Applications - Bresseleers, Jaleesa (Org Process Res Dev, 2019)
[Image: see text] An efficient, scalable, and good manufacturing practice (GMP) compatible process was developed for the production of docetaxel-loaded poly(ethylene glycol)-b-poly(N-2-benzoyloxypropyl methacrylamide) (mPEG-b-p(HPMA-Bz)) micelles. First, the synthesis of the mPEG-b-p(HPMA-Bz) block copolymer was optimized through step-by-step investigation of the batch synthesis procedures. This resulted in the production of 1 kg of mPEG-b-p(HPMA-Bz) block copolymer with a 5 kDa PEG block and an overall molecular weight of 22.5 kDa. Second, the reproducibility and scalability of micelle formation was investigated for both batch and continuous flow setups by assessing critical process parameters. This resulted in the development of a new and highly efficient continuous flow process, which led to the production of 100 mL of unloaded micelles with a size of 55 nm. Finally, the loading of the micelles with the anticancer drug docetaxel was successfully fine-tuned to obtain precise control on the loaded micelle characteristics. As a result, 100 mL of docetaxel-loaded micelles (20 mg/mL polymer and 5 mg/mL docetaxel in the feed) with a size of 55 nm, an encapsulation efficiency of 65%, a loading capacity of 14%, and stable for at least 2 months in water at room temperature were produced with the newly developed continuous flow process. In conclusion, this study paves the way for efficient and robust large-scale production of docetaxel-loaded micelles with high encapsulation efficiencies and stability, which is crucial for their applicability as a clinically relevant drug delivery platform.